If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -2 = y Reorder the terms: -2 + -6x = y Solving -2 + -6x = y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -6x = 2 + y Combine like terms: -2 + 2 = 0 0 + -6x = 2 + y -6x = 2 + y Divide each side by '-6'. x = -0.3333333333 + -0.1666666667y Simplifying x = -0.3333333333 + -0.1666666667y
| |1/4x-2|=4 | | 16=4z+4 | | v/4-16=-12 | | 6y-14/2 | | 2(x-4)+1=3(2-x) | | (X)(X+8)=240 | | 3+0.1(29-x)=1.6x-(0.4x-3.3) | | 20=12+2q | | 5x-2(3-x)=8 | | 13r=5 | | 2=2f-4 | | 6a^2-11a-10= | | U-2/5=2/3 | | 9=2h+1 | | 7+4x=4x-7 | | y=-x^3+9x^2-24+10 | | X-2/3=4/2/5 | | log[5](-7-4x)=2 | | -7+x+2x=-31 | | 5v^2-11v-1=0 | | X-2/3=4(2/5) | | 6k^2-21k= | | 30e^(t/30)(−ln(2)) | | x-1/3-4=x-9/4 | | Y=4(-3)+4 | | 10+10x=10+10x | | X-2/3=42/5 | | -8x-7=-9x+1 | | 10x+5y-2= | | 0=9x+39x+12 | | 4x+4=-4x-20 | | (1+6i)(1+6i)=0 |